Respuesta :

ANSWER

Extraneous solution: x=6

Real solution: x=11

EXPLANATION

The given expression is

[tex] \sqrt{x - 2} + 8 = x[/tex]

Add -8 to both sides:

[tex]\sqrt{x - 2} + 8 + - 8= x + - 8[/tex]

[tex] \implies\sqrt{x - 2} = x - 8[/tex]

Square both sides.

[tex]\implies(\sqrt{x - 2} )^{2} =( x - 8)^{2} [/tex]

[tex]x - 2=( x - 8)^{2} [/tex]

We expand the to get

[tex]x - 2 = {x}^{2} - 16x + 64[/tex]

Write in standard quadratic form.

[tex] {x}^{2} - 16x - x + 64 + 2 = 0[/tex]

[tex] {x}^{2} - 17x + 66 = 0[/tex]

Factor to get:

[tex](x - 6)(x - 11) = 0[/tex]

[tex]x = 6 \: or \: \: x = 11[/tex]

We check for extraneous solutions by substituting each value of x into the original equation.

When x=6

[tex]\sqrt{6 - 2} + 8 = 6[/tex]

[tex]\sqrt{4} + 8 =6[/tex]

[tex]2 + 8 = 10 \ne8[/tex]

Hence x=6 is an extraneous solution.

When x=11

[tex]\sqrt{11- 2} + 8 = 11[/tex]

[tex]\sqrt{9} + 8 = 11[/tex]

[tex]3 + 8 = 11[/tex]

This statement is true.

Hence x=11 is the only solution.